PENGEMBANGAN OBJEK WISATA ALAM BERBASIS KEARIFAN LOKAL BERORIENTASI ETNOMATEMATIKA DI DESA APUAN KECAMATAN SUSUT KABUPATEN BANGLI - I Komang Sukendra; Putu Diah Asrida; Ni Kadek Rini Purwati; I Dewa Putu Juwana; Putu Dessy Fridayanthi; I Made Subrata (Widyadari, 2023)
Nature tourism is a form of recreation and tourism activity that utilizes the potential of natural resources, both in their natural state and after cultivation efforts. The aim of this research is to find out how to develop natural tourism objects based on ethnomathematics-oriented local wisdom and to find out the supporters and obstacles in developing natural tourism objects based on ethnomathematics-oriented local wisdom in Apuan village, Susut District, Bangli Regency. This type of research is qualitative descriptive research. This type of research is phenomological while the data collection techniques used by researchers are interviews, documentation and observation. The informants in this research were village and community officials. The data sources used are primary and secondary data. The research results showed that the cultural dimensions of local wisdom in the attraction of ethnomathematics-oriented local wisdom-based nature tourism in Apuan village came from local sources, local culture and local knowledge. The supporting facilities available for nature tourism based on local wisdom in Apuan village are complete, such as toilets and parking lots which are still in fairly good condition. However, improvements still need to be made in terms of numbers, such as toilet facilities. Inhibiting Factors (1) Accessibility, there is no public transportation for large cars that go directly to tourist attractions in Apuan Village. 2) Amenities, accommodation, health facilities, banks, automated teller machines (ATMs) are not yet available.